2013
DOI: 10.5507/bp.2012.109
|View full text |Cite
|
Sign up to set email alerts
|

Our experience using real-time PCR for the detection of the gene that encodes the superficial lipoprotein LipL32 of the pathogenic leptospires to confirm the acute form of human leptospirosis

Abstract: Aims. To examine biological materials (blood, urine, cerebrospinal fluid) of patients with suspected leptospirosis using real-time PCR for detecting the gene that codes the superficial LipL32 lipoprotein, and to evaluate the contribution of the real-time PCR method for the laboratory diagnosis of the acute form of leptospirosis. Material and Methods. During the monitored period of April 2010 -December 2011, a total of 340 biological materials samples were examined (177x blood plasma, 88x urine, 68x, cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…17 We preferred LipL32 real-time PCR as it can be performed quickly (3 h) compared to the conventional PCR method. 18 Compared to our study, where LipL32 real-time PCR was found to be positive in 9/21, a Uruguayan study 19 showed the diagnostic sensitivity of PCR in comparison with MAT to be only 30%. Many other investigators have reported values close to 50%.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…17 We preferred LipL32 real-time PCR as it can be performed quickly (3 h) compared to the conventional PCR method. 18 Compared to our study, where LipL32 real-time PCR was found to be positive in 9/21, a Uruguayan study 19 showed the diagnostic sensitivity of PCR in comparison with MAT to be only 30%. Many other investigators have reported values close to 50%.…”
Section: Discussioncontrasting
confidence: 85%
“…17 We preferred LipL32 real-time PCR as it can be performed quickly (3 h) compared to the conventional PCR method. 18…”
Section: Discussionmentioning
confidence: 99%
“…In our study, antibodies to two serovars of L. interrogans (Pomona and Grippotyphosa) were the only ones observed in a six-year study, with the range of 800-3200 and 200-3200 titres, respectively, indicating the gradual development of infection in the host organism. Serovar Grippotyphosa was also the most prevalent serovar in horses [40] and humans [41] in the Czech Republic. In contrast, serovars Copenhageni and Icterohaemorrhagiae, transmitted by rats, are usually responsible for infections in Europe [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not used to predict the leptospira serotype in the sample [14]. Kucerova et al investigated 216 leptospirosis suspect patient during 2010 -2011 using real time PCT to determine the gene coding leptospira surface lipoprotein LipP32 to confirm acute form of leptospirosis and achieved positive results in total 14 biological material (9 urine, 4 blood, 1 bronchoalveolar) obtained from 8 (3.70%) patients [15].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%